The Pursuit of Victory : From Napoleon to Saddam Hussein - Bond, Brian (New York Oxford University Press, 1998)
In Western Europe and North America the idea that war can deliberately be used as an 'instrument of policy' has become unfashionable, not least because of the carnage of two World Wars and the Americans' humiliating experience in Vietnam. But wars are still fought. Those who start wars clearly believe they are worthwhile. Why? In this original and provocative study, Brian Bond discusses the successes and failures of military and political leaders in their pursuit of victory over the last two centuries.
Includes Index, Bibliography and Notes.
Originally published: Oxford : Oxford University Press, 1996.
Keywords: Military History, Modern. -- Military Leadership -- Politics and War